Virtual Peer Counseling and Emotional Well-Being Among Distance Learning Students Higher Education - Chinedu Michael Okafhor; Ibrahim A. Dandjuma; Ngozi Patience Ekueme (Generasi Sains Indonesia, 2026)
This study examines the influence of virtual peer counseling on the emotional well-being of distance learning students in Nigerian higher education institutions. The increasing expansion of digital learning environments has intensified concerns regarding emotional isolation, psychological stress, and reduced social connectedness among online learners. Using a quantitative cross-sectional survey design, data were collected from 287 students enrolled in distance learning programs across selected Nigerian universities. The data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis. The findings reveal that virtual peer counseling significantly and positively influences students’ emotional well-being. Peer-based digital interaction was found to strengthen emotional stability, academic motivation, psychological comfort, and social connectedness among students participating in online learning systems. Empathy and emotional communication emerged as the most influential dimensions of peer-support interaction. The study also demonstrates that virtual peer counseling explains a substantial proportion of variance in students’ emotional well-being within distance education contexts. The findings provide important implications for universities and policymakers in developing emotionally supportive and sustainable digital learning environments through structured peer-support initiatives.